THE ETHNIC-RACIAL ISSUES IN STATE SCHOOLS IN THE BRAZILIAN PARAIBANO REGION - Daxenberger, Ana Cristina Silva (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2017)
To educate for ethnic-racial relations is to break with the tacit positioning of the school about the racial discrimination and appreciation and recognize the diversity present in Brazil. Our research aimed to evaluate how education for ethnic-racial relations is being constituted in high schools in three cities: Areia, Alagoa Grande and Remígio / PB. We used a semi-structured questionnaire, answered by 622 students; 4 managers and 12 teachers. We can say that we still need debates on ethnic-racial issues within the school, above all, to overcome discrimination and racial prejudice; offer teacher training and improve the qualification materials to be used in the school.